Analisis Tingkat Efisiensi Penjualan Smartphone Dengan Metode Data Envelopment Analysis (Studi Kasus di Multicom Palembang) - Ferdianto Boenyamin; Achmad Alfian (Widya Teknik, 2020)
The need for Smartphones is now increasing, so that shops selling Smartphones are growing rapidly in the city of Palembang. As a result, shop owners must have a sales strategy as well as the advantages of the facilities offered, so as to attract consumers. Multicom is a small and medium-sized store that sells various Smartphones such as Samsung, Vivo, etc. According to the owner, the number of hp sales has decreased. The decrease in sales is feared to have an effect on store efficiency, so efficiency calculations will be carried out. One method used to measure efficiency is Data Envelopment Analysis (DEA). From the results of the research conducted, it is known that one of Multicom stores does not operate efficiently from May 2018 to July 2018, which has an efficiency level of 0.9516 each; 0,8114; and 0.9394. The main factor that causes Multicom to not operate efficiently is that it has not implemented online-based sales. To increase efficiency, an OLX account was created for the Multicom store. After implementing OLX, Multicom stores have an efficiency value of 1 which means it has been efficient..